Population Projection of Nepal: A Logistic Approach - Adhikari, Khagendra; Raya, Hikmat Bahadur (Journal of Nepal Mathematical Society, 2018)
Population growth is a dynamic process which depends upon many variables which result the population projection as a very complicated task. In this article, we try to project the population of Nepal for upcoming 100 years and also project the trend of population growth for next 300 years. In this projection, we use the Logistic Growth Model, a more realistic model of population projection. Here we use the every 10 years data of census and also calculate all the intermediate year’s data by using the exponential growth model. Thus, we use all together 41 years data in our calculation. By using the least square method to fit the Logistic Model in the past population and using the MATLAB, we calculate the logistic growth rate of population of Nepal is r = 3.9655%. The carrying capacity of Nepal is K = Pmax = 4, 38, 14, 550 and the inflection year at which the population is half of the maximum population (K/2 = 2, 19, 07, 275) of Nepal as 1999 from when the population of Nepal will start to be more stable. The population growth rate will be remarkably reduced around the 2071 and the population of Nepal will start to remain more stable from around 2100. As the area of Nepal, its natural resources and possibilities of the dynamical connectivity between the rapid economically growing neighbors, the future population of Nepal seems to be manageable.